He Hauora! He Hauoro! : the use of taonga pūoro in hauora Māori : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health at Massey University, Palmerston North, New Zealand - Solly, Ruby (Massey University, 2023)
Taonga pūoro, often referred to as the traditional musical instruments of the Māori, hold a deeper significance beyond their musicality. Before colonisation, taonga pūoro were integral to Māori wellbeing and health practices. However, during the period of the Tohunga Suppression Act from 1907 to 1962, taonga pūoro were banned and forced underground. The 1980s saw a revival of taonga pūoro, marking the beginning of a renaissance phase. This resurgence has increased their use by clinicians without whakapapa Māori or those with limited experience in their use. This research aims to explore these factors in greater depth, recognising the dangers associated with the professionalisation of taonga pūoro in the context of hauora. A kaupapa Māori approach was used to examine the uses, philosophies, histories, and practitioners of taonga pūoro within hauora to create a framework of models for Māori hauora practitioners and relevant groups. This qualitative design utilised mātauranga Māori as epistemology and whakapapa as ontology, acknowledging the interconnected nature of te ao Māori and the discipline. The first study, ‘Ngā Pou o Pūoro,’ involved interviews with important figures within taonga pūoro ki hauora. Key themes from this study were te taiao (the environment), pūoro as a means of communication, the role of wāhine as kaitiaki pūoro, and the significance of tīpuna and whakapapa. The findings from this study were translated into the ‘He Hauora! He Hauoro!’ framework for taonga pūoro ki hauora. This framework consists of five models, each focusing on different knowledge areas within taonga pūoro ki hauora, such as practitioner safety, mana wāhine, environment, and experimentation. The framework was then applied in the second study, ‘Taonga Pūoro ki Waihao,’ within a marae-based community context during a wānanga series for whānau. Themes of mana wāhine and wāhine as kaitiaki of taonga pūoro were found to be crucial, along with the relationship with the environment and Indigenous joy. Implications of this research include the use of the ‘He Hauora! He Hauoro!’ framework by Māori and Māori health organisations, including the inclusion of taonga pūoro ki hauora practitioners within hospitals and other public health services as part of the integration of rongoā Māori into healthcare. Recommendations include further research to explore how taonga pūoro can support those with specific health conditions and better enhance overall hauora needs. The research also advocates for increased measures to safeguard taonga pūoro practices for Māori. It is suggested that a form of school or kura be developed to assist with disseminating this knowledge for all Māori, focusing on wāhine, and assisting practitioner development.
Keywords: Māori (New Zealand people); Health and hygiene; Medicine; Music; Musical instruments, Māori; Hauora; Rongoā; Taonga pūoro; Pūmotomoto; Kōauau; mana wāhine; hine raukatauri; rongoā Māori; Māori Doctoral Thesis; 451017 Te oranga ā-pāpori, ā-hinengaro, ā-ahurea, ā-wairua o te Māori (Māori social, cultural, emotional and spiritual wellbeing); 450715 Te puoro me ngā mahi a te rēhia o te Māori (Māori music and performing arts)